Liability in Tort of Financial Supervisory Authorities – a comparative analysis - Bagińska, Ewa (Studia Iuridica Toruniensia, 2019)
The article reviews case law and also provides a theoretical framework for claims of individuals, such as depositors, and financial institutions, who seek monetary compensation against public authorities for failure to supervise the financial market and its institutions. The author presents the core elements of a tort of Financial Supervisory Authorities and analyses the evolution of the standard of liability. Other conditions for a compensatory claim which operate as obstacles to liability (eg. the protective purpose of legal rules and compensable damage) are also discussed. Finally, policy argument pro and on the liability of Financial Supervisory Authorities are recapitulated.